Leaching method of zinc sulfide concentrate

By using alkaline washing + water washing pretreatment technology in zinc resource treatment and the combined use of lignin and iron seed crystals, combined with the removal process of high-speed silicon water quenching slag, the problem of sulfur wrapping and impurity control in zinc resources is solved, and the problem of sulfur packaging and impurity control in zinc resources is improved. The utilization rate and product quality of zinc electrolyte are reduced, and the power consumption and operation risks are reduced.

CN119194093APending Publication Date: 2024-12-27YUNNAN YONGCHANG LEAD & ZINC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317103.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Current zinc resource processing technology has the ability to contain iron, high sulfur, low zinc content, high impurities, pressure leaching slag sulfur package, high arsenic content of electrolyte, system fluorochloro ions and organic matter exceeds the standard, and difficulty in purification and decomposition. Problems of high power consumption and difficult to guarantee output and quality.

Method used

The combined pretreatment technology of alkali washing + water washing combined with lignin and iron seed crystals is used to adjust the amount of surfactant to control the sulfur wrapping and agglomeration phenomenon during pressurized leaching, and remove zinc and oxygen through high-iron silicon water quenching slag The zinc acid ratio of fluorine, chlorine, arsenic and antimony in the powder is adjusted to improve the zinc production and product quality of the electrolyte.

Benefits of technology

The phenomenon of pressure-leached sulfur encapsulation is effectively controlled, the operation risk of pressurized leaching is reduced, the utilization rate of new zinc electrolyte is improved, the viscosity and resistance of electrolyte is reduced, and the zinc production and product quality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194093A_ABST
    Figure CN119194093A_ABST
Patent Text Reader

Abstract

The invention relates to a leaching method of zinc sulfide concentrate, which comprises the following steps: adding lignin and iron precipitation seed crystal into an autoclave filled with the zinc sulfide concentrate, reacting, separating to obtain zinc sulfate leachate and discharged tail gas, introducing the discharged tail gas into a neutral leaching tank, and carrying out neutral leaching on the zinc sulfate leachate to obtain supernate, adding activated carbon into the supernate, and carrying out multi-stage evolution to obtain an electrolyte; zinc oxide powder is pretreated through alkali washing-water washing of high-iron silicon water quenching slag to obtain a zinc source, and zinc ions in electrolyte and the zinc source are recycled in a solid metal form through the electrodeposition process. The method effectively reduces the operation risk of the autoclave, and reduces the unit consumption of the manganese-containing oxidizing agent in the leaching process while balancing and controlling manganese ions of the system; the solution turnover of the system is reduced, the viscosity and resistance of the electrodeposition liquid are reduced, conditions are created for reducing the unit consumption of electrodeposition direct current, the clarity and brightness of the electrodeposition liquid and the zinc precipitation condition are improved, the new liquid utilization rate is more than 80%, and the zinc precipitation yield and the product quality are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of zinc ore processing, and in particular to a method for leaching zinc sulfide concentrate. Background Art

[0002] Due to the shortage of high-quality zinc resources in China, zinc raw materials generally have problems such as high iron and sulfur content and low zinc content in zinc sulfide concentrate, high content of arsenic, antimony, fluorine, chlorine and organic matter in zinc oxide powder, and high content of silicon and iron in crude lead smelting water quenching slag, which are typical difficult-to-process zinc resources. After such raw materials are put into production, there are serious sulfur encapsulation in zinc sulfide pressure leaching slag, high risk of safe operation of pressure autoclave, high arsenic content in zinc leaching solution, excessive content of fluorine and chloride ions and organic matter in the system, difficulty in purification and impurity removal, and frequent "plate burning and re-dissolution" of electrolytic zinc precipitation, resulting in the inability to guarantee product output and quality.

[0003] The oxygen utilization rate in the pressure leaching process is low, and the oxygen content of the exhaust gas is still nearly 90%. At present, almost all the exhaust gas (waste oxygen) of the pressure leaching process of domestic zinc sulfide concentrate is discharged, and there is no relevant report on its recovery and utilization.

[0004] In the neutral leaching process of wet zinc smelting, in order to remove ferrous ions in the zinc sulfate leachate, manganese powder, potassium permanganate, anode mud, etc. are generally used as oxidants to oxidize the Fe2+ ions in the solution into Fe3+ ions. When the pH value of the solution is controlled at 5.2-5.4, Fe3+ is removed by co-precipitation with As, Sb, and Ge ions. This method introduces Mn2+ while oxidizing and removing iron, resulting in excessive Mn2+ in the electrolytic process, a large amount of anode mud, an increase in power consumption, and an increase in the workload of the electrolytic cell. Secondly, when cleaning the anode mud, the anode is deformed, and the Pb content in the solution increases after the oxide film on the anode surface falls off, affecting the chemical quality of the zinc deposited by electrolytic deposition.

[0005] In the process of hydrometallurgical zinc production, various raw and auxiliary materials and various mechanical oil leakage will bring organic matter into the system solution to varying degrees. Currently, organic matter is mainly removed by high-temperature strong oxidation treatment and activated carbon adsorption of organic matter. Although this method can achieve a certain effect of removing organic matter, the process requires high-temperature operation, and has little effect on improving the purification and impurity removal efficiency and reducing the unit consumption of zinc powder.

[0006] At present, the acid-zinc ratio of zinc electrolyte at home and abroad is generally controlled between 2.5 and 4.0:1, and the utilization rate of new solution in the electrolytic process is only 65-68%. The small acid-zinc ratio leads to increased viscosity and resistance of the electrolytic solution, and increased DC power consumption of zinc electrolysis; secondly, it increases the turnover volume of the system solution, increases power consumption and consumption of various auxiliary materials, and increases production costs.

[0007] In summary, the current process technology for difficult-to-treat zinc raw materials has many defects, including limited processing capacity, waste gas not recycled, difficult impurity control, high energy consumption, etc. In order to improve the current situation and make efficient and reasonable use of such domestic zinc resources, a leaching method for zinc sulfide concentrate is invented to achieve comprehensive recycling of difficult-to-treat zinc resources in view of the technical problems arising from the production of difficult-to-treat zinc raw materials. Summary of the invention

[0008] In order to solve or partially solve the problems existing in the related art, the present application provides a leaching method for zinc sulfide concentrate, which removes impurities by adopting a combined pretreatment technology of alkali washing + water washing, improves slag properties by adjusting the amount of surfactant added and crystal seeds, controls the sulfur-encapsulated agglomeration phenomenon in the pressurized leaching process, and controls the acid-zinc ratio in the zinc electrowinning process to improve the precipitated zinc yield and product quality.

[0009] The first aspect of the present application provides a method for leaching zinc sulfide concentrate, comprising the following steps:

[0010] Adding lignin and iron precipitate seeds into a pressure kettle filled with zinc sulfide concentrate, reacting and separating to obtain zinc sulfate leaching solution and exhaust gas, wherein the amount of lignin added is positively correlated with the sulfur content of the zinc concentrate entering the kettle;

[0011] The exhaust gas is passed into the intermediate leaching tank, the zinc sulfate leaching solution is subjected to neutral leaching to obtain a supernatant, activated carbon is added to the supernatant, and then multi-stage evolution is performed to obtain an electrolyte;

[0012] The zinc oxide powder is pretreated by alkali washing and water washing, and high iron silicon water quenching slag is added to remove fluorine, chlorine, arsenic and antimony from the zinc oxide powder to obtain a zinc source, wherein the sodium carbonate concentration of the alkali washing solution during the alkali washing process is 1-2%, the liquid-solid ratio is 3.5:1-10:1, the operating temperature is 70-80 degrees Celsius, and the operating time is 0.5-2 hours;

[0013] The zinc ions in the electrolyte and the zinc source are recovered in the form of solid metal through the electrolytic process. The acid-zinc ratio of the zinc electrolyte during the electrolytic process is 5:1 to 6.5:1.

[0014] The amount of lignin used is not less than 0.3% of the amount of zinc concentrate entering the kettle.

[0015] Among them, the amount of activated carbon is 0.3kg / m3, and the amount of zinc powder is 80kg / 40m3.

[0016] Among them, during the electrolysis process, the current density is 450A / m2, the cycle is 24 hours, the amount of cow glue added is 0.01g / L, and the amount of strontium carbonate added is 0.42g / L.

[0017] In the alkali washing process, the sodium carbonate solution concentration of the alkali washing liquid is 2%, the solid ratio of the alkali washing liquid is 5:1, and the zinc oxide powder is added in a dry manner.

[0018] The amount of iron precipitate seed added is 3-5‰ of the iron content of the zinc sulfide concentrate.

[0019] The amount of high iron silicon water quenched slag added is 5-7% of the iron content of the zinc source.

[0020] The technical solution provided by this application may have the following beneficial effects:

[0021] The present application provides a leaching method for zinc sulfide concentrate, which effectively controls the occurrence of sulfur-encapsulated agglomeration phenomenon in pressurized leaching, reduces the operating risk of the pressure autoclave, and prolongs the operating cycle of the pressure autoclave; utilizes the external exhaust gas to replace part of the manganese-containing oxidant, balances the manganese ions of the system while reducing the unit consumption of the manganese-containing oxidant in the leaching process, and reduces the labor intensity of the clean production cycle management of the electrolytic deposition process; reduces the turnover of the system solution, reduces the viscosity and resistance of the electrolytic solution, creates conditions for reducing the unit consumption of direct current in the electrolytic deposition, improves the clarity of the electrolytic solution and the zinc precipitation condition, and the utilization rate of the new solution is greater than 80%, so that the zinc precipitation output and product quality are greatly improved.

[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0024] Figure 1 It is a schematic flow diagram of a method for leaching zinc sulfide concentrate shown in an embodiment of the present application.

[0025] Figure 2 It is a schematic diagram of the processing flow of high-impurity zinc oxide powder in the leaching method of zinc sulfide concentrate shown in the embodiment of the present application. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0027] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0028] In the description of the present application, it should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0029] Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0030] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.

[0031] Embodiment 1:

[0032] like Figure 1 The leaching method of the zinc sulfide concentrate shown comprises the following steps:

[0033] S1. Add lignin and iron precipitate seeds to a pressure autoclave filled with zinc sulfide concentrate, react and separate to obtain zinc sulfate leaching solution and exhaust gas, wherein the amount of lignin is not less than 0.3% of the amount of zinc concentrate entering the autoclave, and the amount of iron precipitate seeds added is 3-5‰ of the iron content of the concentrate entering the autoclave.

[0034] Iron seed precipitation accelerates the iron precipitation process by providing a crystallization core to promote the formation and growth of iron alum. This method not only improves the iron precipitation efficiency, but also helps to control the particle size and morphology of iron alum, thereby optimizing the efficiency and product quality of the entire leaching process, improving slag properties, controlling the sulfur-encapsulated agglomeration phenomenon during the pressure leaching process, and extending the operation cycle of the pressure autoclave. This process also makes full use of the catalytic effect of iron in the leaching process to accelerate the leaching rate of zinc.

[0035] S2. The exhaust gas is passed into the intermediate leaching tank, and the zinc sulfate leaching solution is neutrally leached to obtain a supernatant, and activated carbon is added to the supernatant to perform multi-stage evolution to obtain an electrolyte. The amount of activated carbon used is 0.3kg / m3.

[0036] S3. Pre-treat the zinc oxide powder by alkali washing and water washing, and add high iron silicon water-quenched slag to remove fluorine, chlorine, arsenic and antimony from the zinc oxide powder to obtain a zinc source. In the alkali washing process, the sodium carbonate concentration of the alkali washing solution is 2%, the liquid-solid ratio is 5:1, the operating temperature is 70-80 degrees Celsius, the operating time is 1 hour, the zinc oxide powder is added in a dry manner, and the amount of high iron silicon water-quenched slag added is based on the iron content of the neutralizer of 5-7%.

[0037] S4. The zinc ions in the electrolyte and the zinc source are recovered in the form of solid metal through the electrolytic process. The acid-zinc ratio of the zinc electrolyte during the electrolytic process is 5:1 to 6.5:1. During the electrolytic process, the current density is 450A / m2, the cycle is 24 hours, the amount of cow glue added is 0.01g / L, and the amount of strontium carbonate added is 0.42g / L.

[0038] Comparative Example 1

[0039] The difference from Example 1 is that in S1, the dosage of lignin is 0.15 and 0.5, and other conditions remain unchanged.

[0040] Under the operating control conditions of 1.2L front liquid volume, 3.9:1 liquid-solid ratio, 180g / L leaching initial acid, 1.2MPa pressure, 120-155℃ operating temperature, and 500r / min stirring speed, the effects of lignin type and dosage on oxygen pressure leaching of zinc sulfide concentrate were determined. The specific test results are shown in Table 1.

[0041] Table 1 Effect of different lignin types and dosages on oxygen pressure leaching of zinc sulfide concentrate

[0042]

[0043] From the above results, it can be seen that the type and amount of lignin used in the oxygen pressure leaching process of the same zinc sulfide concentrate have a significant effect on the oxygen pressure leaching effect. In order to ensure that there is no slag sulfur encapsulation in oxygen pressure leaching and to ensure the safe and stable operation of the autoclave, the amount of lignin usually cannot be less than 0.3% of the amount of zinc concentrate processed. Adding iron precipitation seeds and 0.3% lignin can improve the leaching effect and slag properties of zinc sulfide concentrate. As a surfactant, the amount of lignin added is positively correlated with the sulfur content of the zinc concentrate entering the autoclave. The sulfur content of zinc sulfide concentrate affects the chemical reaction and sulfur encapsulation during pressure leaching. The sulfur element in the zinc sulfide concentrate will be converted from sulfide to sulfate during the pressure leaching process, and sulfur gas will be released. When the sulfur content of the zinc sulfide concentrate is high, more sulfur gas will be produced, which will further promote the condensation and encapsulation of sulfur in the solution. As an additive, lignin can affect the sulfur encapsulation phenomenon by producing a certain chemical reaction or forming a physical barrier. During the pressure leaching process, the addition of an appropriate amount of lignin can provide additional surfactants, increase surface activity, and reduce the occurrence of sulfur encapsulation.

[0044] Comparative Example 2

[0045] The difference from Example 1 is that in S2, a manganese-containing oxidant is directly added to the supernatant of the intermediate leaching during the intermediate leaching operation, and other conditions remain unchanged.

[0046] During the leaching process, the operating conditions were controlled as follows: the volume of the front liquid was 2L, the ratio of the neutralized liquid to the electrolytic waste liquid was 3:1, the operating temperature was 60-70℃, the operating time was 2h, and the end point pH value was 5.0-5.2. The effects of introducing the tail gas (waste oxygen) of the autoclave and directly adding the manganese-containing oxidant on the quality of the supernatant liquid were tested. The specific test results are shown in Table 2 below.

[0047] Table 2 Effects of autoclave tail gas and manganese-containing oxidant on the quality of supernatant

[0048]

[0049] It can be seen from the above test results that the use of pressure autoclave tail gas (waste oxygen) to replace the neutral leaching manganese-containing oxidant can play a good oxidizing role, and the impurity element content of the produced supernatant can reach the supernatant quality standard.

[0050] The final manganese ion content of the production system is enriched to 7.65g / L, exceeding the normal internal control standard of 3-5g / L. The increase of manganese ions in the system causes the viscosity and resistance of the electrolytic solution to increase, the unit consumption of direct current for electrolysis to increase, and the electrolytic anode cleaning cycle to shorten.

[0051] Comparative Example 3

[0052] The difference from Example 1 is that in S2, activated carbon is not added to the supernatant of the intermediate leaching, or activated carbon is added during the intermediate leaching process, and other conditions remain unchanged.

[0053] Under the same operating conditions (temperature 60-70°C, time 60 min, antimony salt dosage 0.017 g / L), the effect of one-stage purification of the same supernatant to remove cobalt and nickel was investigated, and the results are shown in Table 3 below:

[0054] Table 3 Effect of activated carbon on purification and removal of cobalt and nickel

[0055]

[0056]

[0057] From the above test results, it can be seen that under the same operating conditions, when high-impurity zinc oxide powder is put into the production system, it is difficult to remove cobalt and nickel in the supernatant at a medium temperature, but adding a certain amount of activated carbon can improve the effect of removing cobalt and nickel. For the removal of cobalt and nickel at a medium temperature, the amount of zinc powder used in the first purification can be reduced by 30-40kg / 50m3 after adding activated carbon; secondly, the optimal amount of activated carbon is 0.3kg / m3.

[0058] The effect of adding activated carbon during the purification process on the electrolytic process was further investigated. The effects of the new liquid produced by conventional purification and the new liquid produced after activated carbon adsorption on the electrolytic effect were investigated. The test results are shown in Tables 4 and 5.

[0059] Table 4 Effect of activated carbon on zinc electrowinning process

[0060]

[0061] Table 5 Chemical composition of precipitated zinc

[0062]

[0063] From the above results, it can be seen that there is no obvious "plate burning" or "re-dissolution" phenomenon in the new liquid electrolytically precipitated zinc after activated carbon adsorption, the physical and chemical quality is significantly improved, and the DC power consumption is reduced by 300 degrees / ton·zinc.

[0064] Comparative Example 4

[0065] The difference from the first embodiment is that in S3, the zinc oxide powder is not pretreated but directly used in the electrolytic process, and other conditions remain unchanged.

[0066] The chemical composition of zinc oxide powder is shown in Table 6:

[0067] Table 6 Raw material composition

[0068]

[0069] As can be seen from the table above, zinc oxide powder contains high levels of F, Cl, As, and Sb. After direct leaching, the leachate contains up to 800 mg / L F and 13,000 mg / L Cl. According to theory and production practice, high levels of fluorine and chlorine in the solution of the hydrometallurgical zinc smelting system will cause serious corrosion to the cathode and anode plates, increase the lead content of the precipitated zinc, increase the unit consumption of the anode and cathode plates, and make it difficult to strip the precipitated zinc, so that production cannot operate normally. Therefore, if the zinc oxide powder is not pretreated to remove fluorine and chlorine, it cannot be directly put into production.

[0070] The experimental results of the influence of the control conditions of zinc oxygen powder wet alkaline washing pretreatment technology on the removal of fluorine and chlorine are as follows:

[0071] (1) Effect of sodium carbonate concentration on alkaline elution removal of fluorine, chlorine, arsenic and antimony

[0072] The operating conditions are: pre-liquid volume 1L, operating time 1 hour, operating temperature is room temperature, liquid-to-solid ratio is 3.5:1, and stirring speed is 250r / min. Under these conditions, the effect of sodium carbonate concentration on the fluorine and chlorine removal effect of alkaline washing was tested, and the results are shown in Table 7:

[0073] Table 7 Effect of sodium carbonate concentration

[0074]

[0075]

[0076] From the above test results, it can be seen that: under the same operating conditions, the fluorine and chlorine removal rate of zinc oxide wet alkaline washing pretreatment has a slight upward trend with the increase of sodium carbonate concentration, but the overall removal rate is low.

[0077] (2) Effect of liquid-to-solid ratio on the removal of fluorine, chlorine, arsenic and antimony by alkaline washing

[0078] The operating conditions are: pre-liquid volume 1L, operating time 1 hour, sodium carbonate concentration 2%, operating temperature is room temperature, stirring speed 250r / min. Under these conditions, the effect of liquid-solid ratio on the removal of fluorine and chlorine in the alkaline washing process was investigated. The test results are shown in Table 8:

[0079] Table 8 Effect of liquid-solid ratio on impurity removal

[0080]

[0081] From the above test results, it can be seen that: under the same operating conditions, the removal rate of fluorine and chlorine in zinc oxygen powder alkaline washing pretreatment increases with the increase of liquid-to-solid ratio, but the increase is small and the impurity removal rate is still not ideal.

[0082] (3) Effect of temperature on alkaline elution for removal of fluorine, chlorine, arsenic and antimony

[0083] The operating conditions are: pre-liquid volume 1L, operating time 1 hour, sodium carbonate concentration 2%, stirring speed 250r / min, liquid-solid ratio 5:1. Under these conditions, the effect of alkaline washing operating temperature on the removal of fluorine and chlorine was investigated, and the results are shown in Table 9:

[0084] Table 9 Effect of operating temperature

[0085]

[0086]

[0087] From the table above, we can see that under the same conditions, the removal rate of fluorine, chlorine, arsenic and antimony in zinc oxide powder alkaline pretreatment increases with the increase of operating temperature. When the operating temperature is controlled at 70-80℃, the fluorine and chlorine content of zinc oxide powder after alkaline pretreatment can basically meet the requirements for entering the system.

[0088] (4) Effect of operation time on the removal of fluorine, chlorine, arsenic and antimony by alkaline washing

[0089] The operating conditions are: pre-liquid volume 1L, operating time 1 hour, sodium carbonate concentration 2%, operating temperature 70-80℃, stirring speed 250r / min, liquid-solid ratio 5:1. Under these conditions, the effect of alkaline washing operating temperature on the removal of fluorine and chlorine was investigated, and the results are shown in Table 10:

[0090] Table 10 Impact of operation time

[0091]

[0092] It can be seen from the above table that under the same conditions, the removal rate of fluorine, chlorine, arsenic and antimony by zinc oxygen powder alkaline washing pretreatment increases with the extension of operation time, but the increase is smaller after 1 hour.

[0093] Comparative Example 5

[0094] The difference from Example 1 is that in S3, water-quenched slag is not added, and other conditions remain unchanged.

[0095] In view of the problem that some zinc oxide powders contain low Fe and high As, Sb and Ge, the leachate contains high As, Sb and Ge after neutral leaching, which directly affects the quality of the supernatant after entering the intermediate leaching as a slurry. The comparative example 5 experiment concluded that the effect of adding an appropriate amount of water-quenched slag produced in the crude lead smelting process during the neutral leaching of zinc oxide powder on the removal effect of impurities As, Sb and Ge.

[0096] The following is the composition of the water-quenched slag produced by crude lead smelting:

[0097] Table 11 Water quenched slag composition

[0098]

[0099] The control conditions of the one-stage neutral leaching technology of zinc oxide powder are: initial acid is 160-170g / L, operating temperature is 60-70℃, operating time is 60min, the amount of water quenching slag added is added according to the control of the total iron content of the leaching solution to 0.5-1.2g / L, and the pH value of the leaching end point is above 5.2. The test results are shown in Table 12.

[0100] Table 12 Effect of adding water quenching slag

[0101]

[0102] From the above test results, it can be seen that adding an appropriate amount of water-quenched slag in the neutral leaching process of zinc oxide powder can effectively reduce the As, Sb, and Ge content of the leachate, reduce the harm of As, Sb, and Ge to the zinc electrowinning process, and fundamentally improve the quality of the zinc oxide powder leachate. At the same time, it not only effectively recycles the low-grade zinc metal in the water-quenched slag of crude lead smelting, but also solves the environmental risk problem of long-term storage of water-quenched slag.

[0103] Comparative Example 6

[0104] The difference from Example 1 is that in S4, the acid-zinc ratio is 3-4:1, and other conditions remain unchanged.

[0105] In order to reduce the impact of increasing the acid-zinc ratio on production, this production test examined increasing the acid-zinc ratio from the original 3-4:1 to 5-6.5:1, and the other control conditions were controlled as usual. The test results are shown in Table 13:

[0106] Table 13 Statistics of utilization rate of high-acid zinc relative to new liquid

[0107]

[0108] From the above production test, it can be seen that on the basis of deep purification of zinc sulfate solution by adding activated carbon in the purification process, increasing the electrolytic acid-zinc ratio to 5-6.5:1 not only has no significant effect on the quality of precipitated zinc, but also has a significant effect on improving the utilization rate of new liquid and reducing the DC power consumption. According to statistics, the utilization rate of new liquid has increased by about 10% compared with before the adjustment, and the DC power consumption has decreased by about 83kwh / t.Zn compared with before the adjustment.

[0109] Finally, it should be noted that, in this article, relationships such as first and second, etc. are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms include, include or any other variations are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0110] The units described as separate components may or may not be physically separated, and the components shown as units may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the solution of this embodiment.

[0111] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for leaching zinc sulfide concentrate, characterized in that: The following steps are involved: Adding lignin and iron precipitate seeds into a pressure kettle filled with zinc sulfide concentrate, reacting and separating to obtain zinc sulfate leaching solution and exhaust gas, wherein the amount of lignin added is positively correlated with the sulfur content of the zinc concentrate entering the kettle; Passing the exhaust gas into a mid-immersion tank, neutrally leaching the zinc sulfate leaching solution to obtain a supernatant, adding activated carbon to the supernatant and performing multi-stage evolution to obtain an electrolyte; The zinc oxide powder is pretreated by alkali washing and water washing, and high iron silicon water quenching slag is added to remove fluorine, chlorine, arsenic and antimony from the zinc oxide powder to obtain a zinc source, wherein the sodium carbonate concentration of the alkali washing solution during the alkali washing process is 1-2%, the liquid-solid ratio is 3.5:1-10:1, the operating temperature is 70-80 degrees Celsius, and the operating time is 0.5-2 hours; The zinc ions in the electrolyte and the zinc source are recovered in the form of solid metal through an electrolytic process, and the acid-zinc ratio of the zinc electrolyte in the electrolytic process is 5:1 to 6.5:

1.

2. The leaching method of zinc sulfide concentrate according to claim 1, characterized in that: The amount of the lignin used is not less than 0.3% of the amount of the zinc concentrate fed into the kettle.

3. The leaching method of zinc sulfide concentrate according to claim 1, characterized in that: The amount of activated carbon used is 0.3kg / m3, and the amount of zinc powder used is 80kg / 40m3.

4. The leaching method of zinc sulfide concentrate according to claim 1, characterized in that: During the electrowinning process, the current density is 450 A / m2, the cycle is 24 hours, the amount of cow glue added is 0.01 g / L, and the amount of strontium carbonate added is 0.42 g / L.

5. The leaching method of zinc sulfide concentrate according to claim 1, characterized in that: During the alkali washing process, the sodium carbonate solution concentration of the alkali washing liquid is 2%, the solid ratio of the alkali washing liquid is 5:1, and the zinc oxide powder is added in a dry manner.

6. The method for leaching zinc sulfide concentrate according to claim 1, characterized in that: The amount of the iron precipitate seed added is 3-5‰ of the iron content of the zinc sulfide concentrate.

7. The method for leaching zinc sulfide concentrate according to claim 1, characterized in that: The amount of the high iron silicon water quenching slag added is 5-7% of the iron content of the zinc source.